FROM THE RIOPLATENSE BORDER TOWNS AND PORT CITIES TO THE GERMAN SETTLEMENTS: SOCCER AND IDENTITYIN RIO GRANDE DO SUL, BRAZIL. (Fiep Bulletin - online, 2013)
This study analyzed the appearance of soccer teams in Rio Grande do Sul, one of the pioneering states in the practice of this sport and a leader in the foundation of soccer clubs. It also studied the expansion of soccer club formation from the border along Rioplatense countries and port cities to immigrant settlements, analyzed the origins of these clubs and discusses the association between the typically Gaucho style of playing soccer and Gaucho identity.
Keywords: Soccer; identity; community; club; management